The influence of temperature on methane adsorption in coal: A review and statistical analysis - Zhijun Wang; Xiaojuan Wang; Weiqin Zuo; Xiaotong Ma; Ning Li (Adsorption Science & Technology)
The capacity of coal to adsorb methane is greatly affected by temperature and, in recent years, temperature-dependent adsorption has been studied by many researchers. Even so, comprehensive conclusions have not been reached and conflicting experimental results are common. This paper reviews the current state of research regarding the temperature-dependent adsorption of methane in coal and catalogs the conclusions from experiments conducted on that subject by 28 researchers, as published between 1995 and 2017. Probability theory and statistics are used to show that the conclusion generally accepted by most researchers is that the amount of methane adsorbed by coal decreases with increasing temperature. It is highly likely that the Langmuir volume decreases as the temperature rises, and it is also probable that the Langmuir pressure increases at higher temperatures. Equations are presented that express the relationships between methane adsorption, Langmuir volume, Langmuir pressure, and temperature. Future research should be directed toward determining the relationship between Langmuir pressure and temperature. The results of the study presented herein provide a theoretical basis for predicting the gas content in coal seams and improving the efficiency of coalbed methane development.